Kontribusi Kegiatan Ekstrakurikuler Pramuka dalam Membentuk Karakter Disiplin Siswa Berdasarkan Norma Sekolah Di SDN 2 Tolitoli - Muh Khaerul Ummah Bk; Putri Pratiwi; Nabila L Latrey; Adrizkal (Alma Ata University Press, 2026)
Disciplinary character education is an essential foundation for students' academic success; however, there is often a gap between informal value cultivation and compliance with formal school regulations. The urgency of this research is driven by the limited studies specifically bridging how Scouting extracurricular mechanisms transform honor code values into concrete behaviors aligned with school rules. This study aims to analyze the specific contribution of Scouting activities in shaping students' disciplinary character at SDN 2 Tolitoli. The research method employed is descriptive qualitative. Data were collected through direct observation, documentation, and in-depth interviews with instructors, classroom teachers, and students. Data analysis techniques followed the Miles and Huberman model, including data reduction, data display, and conclusion drawing. In this study, it is emphasized that school norms are positioned as the primary indicator to measure students' discipline levels, rather than as a separate variable. The results indicate that structured activities such as scout drills (PBB), assemblies, and troop assignments contribute significantly to character building. This is evidenced by four key indicators: time discipline (25%), compliance with school rules/norms (25%), self-discipline and responsibility (20%), and the active role of Scouting activities (30%). The internalization of Dasa Dharma and Trisatya values successfully fostered more punctual, orderly, and responsible student behavior. It is concluded that Scouting is an effective strategic instrument for synergizing character education with the enforcement of formal norms within the school environment